Analyzing The Electromagnetic Transients and Corona Performance of Long Overhead Lines with Multiple Tower Spans - Mohamed M. Saied (International Journal of Electrical and Communication Engineering Technology, 2025)
This paper addresses the simulation of the electromagnetic transients developed in an important class of non-uniform high voltage power lines. The resulting information is of paramount importance for the proper planning, design, operation and protection of electric power networks. It deals particularly with long overhead high voltage transmission lines composed of several tower spans which are connected in cascade. The presented approach considers eventually existing localized corona discharges at some points along the line. The derived mathematical model leads to a system composed of two simultaneous differentials as well as several algebraic equations which can be solved numerically in terms of parametric functions using the software Mathematica using the statement (ParametricNDSolve). The location, the Laplace operator, and the loading conditions of the lines will all affect the resulting current and voltage distributions along the line. To obtain the appropriate findings in the time domain using the well-known Hosono algorithm, the paper offers a code for the numerical Laplace inversion of these formulas. This code has already been tested and validated in several studies that are available in literature. By contrasting the outcomes of the case studies that are supplied with those that are accessible elsewhere, the model and computer code are verified. It is believed that this study will be helpful to the high voltage and protection engineers in addition to power engineering students and trainees.
Keywords: Corona; Non-Uniform; Numerical Laplace Inversion Hosono algorithm; Parametric Functions; Simulation; Span; differential equations; electromagnetic; high voltage lines; mathematica; parameter study; towers; transients